2022
DOI: 10.1097/pxr.0000000000000100
|View full text |Cite
|
Sign up to set email alerts
|

From outcome measurement to improving health outcomes after lower limb amputation—A narrative review exploring outcome measurement from a clinical practice perspective

Abstract: Outcome measurement is essential to understand the impact of clinical interventions and the performance of services. Despite national and professional body encouragement, and successful examples of system level outcome measurement within some health care settings, many barriers still exist preventing outcome measurement from becoming embedded in clinical practice. This paper presents a narrative review which aims to describe the state of the outcome measurement evidence base in prosthetic rehabilitation, as ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…The recommendations also include many outcome measures capturing the same outcome domain (i.e., mobility via measures such as the Six Minute Walk test, Timed Up and Go, or the Amputee Mobility Predictor). A recent narrative review highlighted the absence of outcome measure consensus in the field of prosthetic rehabilitation, and suggested it may be driven by a lack of understanding around which outcome domains characterise a meaningful recovery following prosthetic rehabilitation, and should therefore be measured [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The recommendations also include many outcome measures capturing the same outcome domain (i.e., mobility via measures such as the Six Minute Walk test, Timed Up and Go, or the Amputee Mobility Predictor). A recent narrative review highlighted the absence of outcome measure consensus in the field of prosthetic rehabilitation, and suggested it may be driven by a lack of understanding around which outcome domains characterise a meaningful recovery following prosthetic rehabilitation, and should therefore be measured [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Clinical outcome measures that are self-reported questionnaires (e.g., Activities-Specific Balance Confidence) or functional mobility tests (e.g., Timed Up and Go [TUG]) are clinically feasible ways to potentially evaluate fall risk, but there is still no consensus on which clinical outcome measures are most important for evaluating fall risk for general prosthetic rehabilitation. 27,28 Studies in non-prosthetic populations have suggested gait assessments may be stronger indicators of fall risk than clinical outcome measure scores 32,33 or could supplement clinical outcome measure scores 34,35 to improve fall risk screening. Therefore, gait assessments that are spatiotemporal (e.g., walking speed), kinematic (e.g., joint angles), or kinetic (e.g., joint moments or powers) may also be useful to evaluate fall risk in older adults who use lowerlimb prostheses.…”
Section: Introductionmentioning
confidence: 99%